2010
DOI: 10.1021/ci100068w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analyses on Binding Affinity of Substituted Benzenesulfonamides with Carbonic Anhydrase Using ab Initio MO Calculations on Their Complex Structures

Abstract: Quantitative structure-activity relationship analyses on the free energy change during complex formation between substituted benzenesulfonamides (BSAs) and bovine carbonic anhydrase II (bCA II) were performed using generilized Born/surface area (GB/SA) and ab initio fragment molecular orbital (FMO) calculations for the whole complex structures. The result shows that the overall free energy change is governed by the contribution from solvation and dissociation free energy changes accompanying by complex formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 96 publications
5
45
0
Order By: Relevance
“…Fischer et al 555 improved the scoring functions representing the binding energy for human estrogen receptor subtype R and human retinoic acid receptor of isotype γ, using atomic charges from FMO calculations at the RHF/STO-3G level and concluded that such quantum scoring functions (QSF) describe the electrostatics accurately, and that QSF performs better than force field analogues. Yoshida et al 556 applied FMO/RHF/6-31G to QSAR studies of the binding affinity of substituted benzenesulfonamides with carbonic anhydrase, noting the difficulties in modeling Zn 2+ -containing systems. Hitaoka et al 557 used FMO/ MP2/6-31G in QSAR studies of the binding affinity of sialic acid analogues with influenza virus neuraminidase-1, where they divided the protein into three binding pockets and used the sums of PIEs for these subsystems as separate descriptors.…”
Section: δEmentioning
confidence: 99%
“…Fischer et al 555 improved the scoring functions representing the binding energy for human estrogen receptor subtype R and human retinoic acid receptor of isotype γ, using atomic charges from FMO calculations at the RHF/STO-3G level and concluded that such quantum scoring functions (QSF) describe the electrostatics accurately, and that QSF performs better than force field analogues. Yoshida et al 556 applied FMO/RHF/6-31G to QSAR studies of the binding affinity of substituted benzenesulfonamides with carbonic anhydrase, noting the difficulties in modeling Zn 2+ -containing systems. Hitaoka et al 557 used FMO/ MP2/6-31G in QSAR studies of the binding affinity of sialic acid analogues with influenza virus neuraminidase-1, where they divided the protein into three binding pockets and used the sums of PIEs for these subsystems as separate descriptors.…”
Section: δEmentioning
confidence: 99%
“…We previously proposed a novel QSAR procedure called linear expression by representative energy terms (LERE)-QSAR [17][18][19][20][21] involving molecular calculations such as an ab initio fragment molecular orbital (FMO) one.…”
Section: Formulation Of the Lere-qsar Equationmentioning
confidence: 99%
“…The X-ray structures of CAs have shown that the zinc ion (Zn +2 ) within the active site is coordinated to three histidine residues and one water molecule (or hydroxide anion) and that the water molecule is replaced by a CA inhibitor as the fourth ligand of Zn +2 . 8 One of the most prominent classes of CA inhibitors is aromatic/heterocyclic sulfonamides which have been studied for the development of antiglaucoma, antitumor, antiobesity or anticonvulsant drugs 9 . Quantitative structure-activity relationship (QSAR) studies generally perform a vital role in drug discovery and design as ligand-based approaches 10 .…”
Section: E Znmentioning
confidence: 99%